Application of Blockchain Technology in Cross-Border Telecommunications Network Fraud to Ensure China’s Judicial Justice - Chen Siqi; Ramalinggam Rajamanickam; Nazura Abdul Manap; Zamre Mohd Zahir (Jurnal IUS Kajian Hukum dan Keadilan, 2024)
Cross-border telecommunication fraud involves criminals abroad using network technology to remotely defraud Chinese citizens. China is currently facing more severe problems in combating cross-border telecommunications network fraud, including the easy destruction of electronic evidence during the process of collecting and storing evidence, low investigation efficiency in cross-border judicial cooperation, and the difficulty in tracing stolen money involved in cases located abroad. In order to combat crime and achieve judicial justice, investigators need to use the latest science and technology to improve case handling efficiency, and blockchain technology is exactly what they are paying attention to. Blockchain technology, as an emerging technology, has the characteristics of decentralization and non-tampering, and has unique advantages in the acquisition, storage and circulation of data. Therefore, this article aims to explore the necessity and feasibility of applying blockchain technology to combat cross-border telecommunication network fraud. This article adopts qualitative approaches to analyze the current Chinese legal provisions and research literature on the field of cross-border telecommunication network fraud, and provides a comprehensive understanding of blockchain technology. This article proposes leveraging the characteristics of blockchain technology to prevent telecommunication network fraud by establishing a personal information protection mechanism and a suspicious fund flow supervision mechanism through blockchain technology. Furthermore, the efficiency of investigation can be improved by establishing an internal communication and cooperation mechanism. The authenticity and integrity of evidence can be ensured by establishing blockchain forensics and evidence storage system.